The Lambkins - Bunting, Eve, 1928-; Keegan, Jonathan (New York : Joanna Cotler Books, 2005)
After being kidnapped by the lonely widow of a brilliant geneticist, Kyle finds himself shrunk to doll-size and living with three other children in a dollhouse from which there seems to be no escape
Teenager ages 13-18 years old (blue)
Keywords: Dollhouses -- Fiction; Genetic engineering -- Fiction; Kidnapping -- Fiction